2017
DOI: 10.1590/s0100-204x2017000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters and cluster analyses for carcass and meat quality traits in birds

Abstract: -The objective of this work was to estimate genetic parameters for bird carcass and meat quality traits, as well as to explore the genetic patterns of the breeding values of this population using cluster analyses. Data from 1,846 birds were used to estimate the genetic parameters of production and quality traits using the multiple-trait animal model, and cluster analyses were performed. The heritability estimates ranged from 0.08±0.03 for meat pH measured 24 hours after slaughter to 0.85±0.09 for body weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In general, the heritability estimates were moderate for WEIGHT, LOSSES, COLOUR, and VISCERA, ranging from 0.18 to 0.39. These heritabilities are in agreement with the results of other studies (Alnahhas et al, 2016;Bainy et al, 2017;Chu et al, 2020;Gaya et al, 2006). These authors reported heritability values ranging from 0.20 to 0.48, 0.25 to 0.31, 0.12 to 0.22, and 0.13 to 0.29 for traits covered in the variables WEIGHT, VISCERA, COLOUR, and LOSSES, respectively.…”
Section: Bayesian Multiple-trait Animal Modelsupporting
confidence: 91%
“…In general, the heritability estimates were moderate for WEIGHT, LOSSES, COLOUR, and VISCERA, ranging from 0.18 to 0.39. These heritabilities are in agreement with the results of other studies (Alnahhas et al, 2016;Bainy et al, 2017;Chu et al, 2020;Gaya et al, 2006). These authors reported heritability values ranging from 0.20 to 0.48, 0.25 to 0.31, 0.12 to 0.22, and 0.13 to 0.29 for traits covered in the variables WEIGHT, VISCERA, COLOUR, and LOSSES, respectively.…”
Section: Bayesian Multiple-trait Animal Modelsupporting
confidence: 91%